THE CORRELATION BETWEEN STUDENTS’ META-LEARNING AWARENESS AND WRITING DESCRIPTIVE TEXT IN JUNIOR HIGH SCHOOL - Aisha Zhamasar; Juwita Boneka Sinaga; Erwin Ashari (Universitas PGRI Sumatera Barat, 2025)
This study aims to investigate the relationship between students’ Meta-learning awareness and writing descriptive texts at the junior high school level. This research is motivated by students' difficulties in writing descriptive texts, including organizing ideas, selecting vocabulary, and applying correct grammar. The research method used is a quantitative approach with a correlational design. The population of this study consisted of all seventh-grade students at SMPN 30 Batam, and one class (N = 41) was randomly selected using a cluster random sampling technique. The research instruments consist of a questionnaire to measure Meta-learning awareness and a writing test to assess the ability to write descriptive texts based on Brown's (2003) rubric. The data was analyzed using the Spearman rank correlation test because the data was not normally distributed. The analysis results show a significant positive correlation between Meta-learning awareness and writing descriptive text (rs = 0.330; Sig. = 0.035). Although the strength of the correlation is considered weak, this finding indicates that students with higher Meta-Learning awareness tend to have better writing skills. The results of this study confirm that Meta-learning awareness can improve students' writing skills by encouraging them to be more reflective in the learning process. This research recommends that teachers integrate Meta-learning activities into writing instruction to foster students' independence, focus, and confidence in producing descriptive texts.